Challenges Faced by Working Mothers and Housewives during Online Education of their Children - Qudsia Umaira Khan, Amna Nadeem, Muallah, Nighat Nadeem, Maryam Rao, Junaid Sarfraz, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: WHO recognized COVID-19 a pandemic on March 12, 2020 and National Health Commission officially declared it as a Class-B infectious disease. The technological advancements enabled the teaching staffs to keep their students involved during this period of COVID-19 pandemic. Online classes become the efficient medium to learn by staying at home. Aim: To find out the challenges faced by mothers during online learning in order to devise a systematic plan for smooth and effective learning in case of another crises like COVID-19. Method: It was a cross sectional study carried out at CMH LMC&IOD , in which a user-defined questionnaire was introduced to the participants which were mothers of school going children from all over the city. The questionnaire got 161 responses in total, but two were incomplete so 159 were considered while doing the analysis. The results were analyzed using SPSS25. Results: In this study,46.9% mothers were of age 40 and above and 47.5% were between 31 -40 years of age. Rest were 30 and below 57.5 % children used laptops to study online, while 34.4 % used a mobile. 7% had their own tablets and only 1.1 used desktops. Only 14.4% mothers supervised their children during all this time. 58.7% however managed supervising studies with other tasks and 26.9% said their children could study online unsupervised. Only 20% mothers thought their children are taking interest in online schooling. 54.5% found their children struggling37.5% mothers thought that their children were learning much less through this online mode of education and 43.8% thought that online learning is somewhat less. Conclusion: Among the various the challenges faced by working mothers and housewives during online education of their children the most important challenge was to keep their children focused on study. We discovered that the online study had little effect on grades because most mothers had to take on the role of teacher as well as supervising.